THE IMPACT OF HUMAN RESOURCE COMPETENCY GAPS ON TOURIST EXPERIENCES AT DESTINATIONS NIRWANA LAKE NATURE TOURISM DESTINATION, ROTE NDAO REGENCY - Irience R.A. Manongga; Anastasia Imelda Sayd (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine and analyze the influence of advertising techniques and visual advertising appeal on the purchasing decisions of Kavawear clothing products on the TikTok Shop platform among consumers in Tangerang City. Methods: This research is a quantitative study involving 135 respondents selected through a non-probalility convenience sampling technique. Data were gathered using structured questionnaires and processed through multiple linear regression analysis, including validity, reliability, and classical assumption tests using SPSS version 23.0 software. Results: The partial analysis results show that advertising techniques significantly influence purchasing decisions with a t-count of 14.783 > 1.978. Furthermore, visual advertising appeal also has a significant effect with a t-count of 13.623 > 1.978. simultaneously, both variables show a significant impact (F-count 195.623 > 3.06) and contribute 74.4% to the variation in purchasing decisions, while the remaining 25.6% is influenced by other factors. Conclusion and suggestion: This research concludes that the synergy between clear advertising messages and high visual aesthetics is essential in driving consumer conversion on social commerce platforms. Brand managers are encouraged to focus on both informative content and visual quality to optimizr sales performance.